General and efficient route to 3 `-deoxy-3 `-N-, S-, and C-substituted altropyranosyl thymines from 2',3'-O-anhydro-mannopyranosylthymine - Deshpande, Sachin G.; Pathak, Tanmaya (Tetrahedron, 2007)
An efficient route to 1-(2,3-O-anhydro-4,6-O-phenylmethylene–D-mannopyranosyl) thymine from 1,2,4,6-tetra-O-acetyl-3-O-tosyl-beta-D-glucopyranose has been devised. This newly synthesized epoxide is opened up regioselectively at the C-3'-position by N-, S-, and C-nucleophiles to afford a wide range of new 3-deoxy-3'-substituted altropyranosyl thymines. (c) 2006 Published by Elsevier Ltd.

Studies on the synthesis and unusual behavior of vinyl sulfone-modified hexenopyranosylthymines - Deshpande, Sachin G.; Suresh, Cheravakkattu G.; Pathak, Tanmaya (Carbohydrate Research, 2008)
Although vinyl sulfone-modified- (VSM) pent-2-enofuranosyl nucleosides 2 and hex-2-enopyranosyl glycoside 4 are easily synthesized from the corresponding mesylated sulfones le and 3c, respectively, via an oxidation-mesylation-elimination route, the 3'-C-sulfonyl-hex-2'-enopyranosylthymine 11 is not obtained from 10 and a glycal derivative 12 is formed instead. On the other hand, 3-C-sulfonyl-hex-3'-enopyranosylthymine 20 is easily synthesized from the mesylated sulfone 19. Again unlike the reaction patterns of VSM-pent-T-enofuranosyl nucleosides 2 and hex-2-enopyranosyl glycosides 4 as Michael acceptors, the reactions of nucleophiles with 3'-C-sulfonyl-hex-3'-enopyranosylthymine 20 yielded a rearranged product 21 instead of Michael adducts. (c) 2008 Published by Elsevier Ltd.
Keywords: glycal; hexopyranosyl nucleosides; Michael addition; unsaturated nucleosides; vinyl sulfone-modified nucleosides